1999
DOI: 10.1046/j.1365-2796.1999.0448e.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diabetes mellitus on patients with acute intermittent porphyria

Abstract: This study raises the possibility that diabetes mellitus may be beneficial for patients with severe AIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…We have previously suggested that diabetes mellitus may benefit patients with AIP, as acute attacks of AIP became significantly more rare after the onset of diabetes mellitus [24, 25]. In line with this finding, acute attacks of AIP may be successfully treated with glucose.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…We have previously suggested that diabetes mellitus may benefit patients with AIP, as acute attacks of AIP became significantly more rare after the onset of diabetes mellitus [24, 25]. In line with this finding, acute attacks of AIP may be successfully treated with glucose.…”
Section: Discussionmentioning
confidence: 57%
“…Three subjects with high levels of HbA1c were 58–60 years of age (2 without previous episodes of porphyria and 1 with previous attacks of porphyria), while 4 AIP gene carriers were 35–42 years of age, 3 of them were brothers. In previous studies [24, 25], we found a prevalence of 2.2–4.9% of diabetes mellitus in AIP gene carriers. It is surprising to find such a high frequency of AIP gene carriers with increased HbA1c levels, as the AIP gene carriers included in this study have the same gene mutation (W198X) as the Swedish AIP gene carriers studied earlier [24, 25].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This in turn leads to an accumulation of porphyrin precursors prior to porphobilinogen deaminase. The pathogenesis of AIP is not known, but it is suggested that the lack of heme, or an accumulation of porphyrin precursors affecting the nervous system, is chiefly responsible for the clinical expression of AIP (12,56). In many patients, the onset of acute AIP attacks can be aborted by adequate nutritional intake (12).…”
Section: Discussionmentioning
confidence: 99%
“…49 Induction of ALA-S1 Via Metabolic Signaling Some nuclear signaling, such as peroxisome proliferatoractivated receptor-gamma coactivator 1α (PGC-1α), which is involved in a different manner in the endogenous regulation of many metabolic pathways, can take part in the global inductive process of the ALA-S1 activation, which explains why the ALA-S1 transcription is also controlled by some endocrine-metabolic circuits (starvation, gonadal activity, activity of the hypothalamic-hypophysis-adrenal axis, hormone signaling, etc), whose interference may have porphyrogenic effects. 34,40,[50][51][52][53][54] Induction of ALA-S1 Via the Induction of Heme-Oxygenase Expression Agents or conditions that upregulate heme oxygenase, the main enzyme of heme catabolism, may be considered as porphyrogenic; they cause an increase in heme catabolism, thus reducing free heme pool concentrations and activating ALA-S1 transcription. Well-known inducers of HO-1 are stress, fasting, endotoxins, heavy metals, and organic solvents.…”
Section: Mechanisms Of Drug Porphyrogenicitymentioning
confidence: 99%